Comparisons of short-term and long-term results between laparoscopic between open pancreaticoduodenectomy for pancreatic tumors: A systematic review and meta-analysis - Qiu, Hongquan; Zhang, Liang; Wang, Dongzhi; Miao, Haiyan; Zhang, Yu (Frontiers in Genetics, 2023)
Objective: The efficacy of pancreaticoduodenectomy and open pancreaticoduodenectomy for pancreatic tumors is controversial. The study aims to compare the efficacy of laparoscopic pancreaticoduodenectomy (LPD) and open pancreaticoduodenectomy (OPD) in the treatment of pancreatic tumors through systematic evaluation and meta-analysis. Methods: PubMed, Embase, Cochrane Library and Web of science databases were searched for clinical studies on the treatment of pancreatic tumors with LPD and OPD. The end time for the searches was 20 July 2022. Rigorous inclusion and exclusion criteria were used to screen the articles, the Cochrane manual was used to evaluate the quality of the included articles, and the stata15.0 software was used for statistical analysis of the indicators. Results: In total, 16 articles were included, including two randomized controlled trials and 14 retrospective studies. Involving a total of 4416 patients, 1275 patients were included in the LPD group and 3141 patients in the OPD group. The results of the meta-analysis showed that: the operation time of LPD was longer than that of OPD [WMD = 56.14,95% CI (38.39,73.89), p = 0.001]; the amount of intraoperative blood loss of LPD was less than that of OPD [WMD = −120.82,95% CI (−169.33, −72.30), p = 0.001]. No significant difference was observed between LPD and OPD regarding hospitalization time [WMD = −0.5,95% CI (−1.35, 0.35), p = 0.250]. No significant difference was observed regarding postoperative complications [RR = 0.96,95% CI (0.86,1.07, p = 0.463]. And there was no significant difference regarding 1-year OS and 3-year OS: 1-year OS [RR = 1.02,95% CI (0.97,1.08), p = 0.417], 3-year OS [RR = 1.10 95% CI (0.75, 1.62), p = 0.614%]. Conclusion: In comparison with OPD, LPD leads to less blood loss but longer operation time, therefore the bleeding rate per unit time of LPD is less than that of OPD. LPD has obvious advantages. With the increase of clinical application of LPD, the usage of LPD in patients with pancreatic cancer has very good prospect. Due to the limitations of this paper, in future studies, more attention should be paid to high-quality, multi-center, randomized controlled studies.